Genome-Wide Identification and Expression Profiling of Ascorbate Peroxidase (APX) and Glutathione Peroxidase (GPX) Genes Under Drought Stress in Sorghum (Sorghum bicolor L.) - (:unkn) unknown (SPRINGER, 2018)
APX and GPX are two crucial plant antioxidant enzymes. By protein homology search, nine APX and seven GPX members were identified in Sorghum bicolor genome. They were annotated based on chromosomal localizations as SbAPX1-9 and SbGPX1-7. APXs were distributed on six Sorghum chromosomes and encoded polypeptides of 250-474 residues with characteristic peroxidase domain, whereas GPXs were on five chromosomes and encoded proteins of 136-232 residues characterized by a GSHPx domain. The first about 1-90 amino acid residues in SbAPXs and about 60-70 amino acid residues in SbGPXs from N-terminus corresponded to transit peptides, and formed the main source of sequence variations. On the other hand, APXs/GPXs appeared to be significantly conserved at the amino acid sequence level. Residues in active and/or metal binding sites of these enzymes were also revealed with inference to their Arabidopsis counterparts. The combined Sorghum-Arabidopsis APX and GPX phylogenies allowed inferring functional roles to putative Sorghum sequences at cross-species level. In digital RNA-seq data from Sorghum, APXs within sensitive genotypes were relatively more responsive to drought compared to GPXs. Differentially upregulated APX4 and downregulated GPX2 suggested that their performance was synergistic. SbAPXs/GPXs expression in drought-exposed sorghum roots and leaves were quantified by Real-Time quantitative PCR (RT-qPCR). Drought-exposed plants morphologically demonstrated reductions in stem/root elongation and size, retardation in plant growth, and erected leaves. Expressions of APXs/GPXs were mostly upregulated in aboveground parts of drought-exposed plants, e.g., leaves while they were downregulated in roots. Furthermore, APX1 and APX5 in leaves, and APX8, APX9, GPX5, and GPX6 in roots showed significant changes in expression levels; therefore, their synergetic regulation during drought should be considered.
Keywords: Drought; Antioxidant enzymes; ROS; Sorghum; Gene expression; CU/ZN-SUPEROXIDE DISMUTASE; ARABIDOPSIS-THALIANA; ANTIOXIDANT ENZYMES; OXIDATIVE STRESS; PLANT-RESPONSES; LEAF SENESCENCE; TOLERANCE; SEQUENCE; METABOLISM; OVERPRODUCTION